Ellis-Van Creveld syndrome: a case report - Kunte, Nisarga B.; Navale, Rakesh Amruth (International Journal of Contemporary Pediatrics, 2022)
Ellis-Van Creveled (EVC) syndrome, also called chondroectodermal dysplasia, is a rare genetic disorder with autosomal recessive type of inheritance with 25% risk of transmission to subsequent pregnancies. The syndrome is due to mutation of EVC1 and EVC2 genes on chromosome 4p16, characterized by acromesomalic dwarfism, bilateral postaxial polydactyly, ectodermal dysplasia affecting nails, teeth and congenital heart malformation. One third of the patients die at an early age or during infancy from cardio respiratory problems. The birth prevalence of EVC syndrome is 1/5000 live births in Amish population and 7/1,000,000 live birth in non-Amish population. There are a very few case reports in the literature. We reported a case of 14-year male presenting with typical features of this syndrome.